EVALUASI SISTEM PELAYANAN PESAWAT DENGAN TARIF YANG BERBEDA TERHADAP TINGKAT KEPUASAN PENUMPANG - Rahman, Rahmatang (MEKTEK, 2009)
Growth and improvement of airline service from year to year progressively becomes the society’s attention. These things, can be seen from tightening of emulation of service quality, price, promotion among so much airline him. The plane role as transportation medium become progressively the necessary for world, what directly support international business and tourism. In a condition tight emulation, especial matter which must be given high priority by airline is customer satisfaction/ passenger can stay, vieing with to master market compartment. Airline have to know things any kind of lionized by all airline and passenger yield performance as good possible so that can customer gratify. On that account require to be importance and performance analysis.In this research data analyze used by method of discriptive qualitative quantitative. To answer formulation of problem until how far mount customer satosfaction/ passenger to airline performance pursuant to subdividing of tariff (cheap, medium, and expensive), hence used by Analysis Level Have interest and Performance / customer satisfactionFrom result of this research is obtained by formulated elements level and divided to become four part of into diagram of kartesius so that known relation between importance of cutomer to level satisfaction of airline service